Acardiac acephalus with malformed donor twin - Panchbudhe, Shruti; Satia, Meena; Kambhampatti, Lalita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Some specific cases of Acardiac twins observed in remote parts of India where foetuses have been found to have extra limbs jutting out of chest cavity or abdomen have been given the specific and an attractive name of god baby. The present case under discussion is one such case where an Acardiac twin with Acephalus in the parasitic twin and malformed donor twin with multiple congenital anomalies incompatible with life delivered spontaneously at a tertiary care centre.